Soru:
n 16 E) 12 2. f(2x + 3) = x³ - 2x² + 1 olduğuna göre, f'(-1) kaçtır? A) 12 B) 11 C) 10 2 2. (3x² - 4x) 3+h D) 9 3 E) 8 20 IC 2.
![n
16 E) 12
2.
f(2x + 3) = x³ - 2x² + 1
olduğuna göre, f'(-1) kaçtır?
A) 12
B) 11
C) 10
2
2. (3x² - 4x)
3+h
D) 9
3
E) 8
20
IC
2. f(x)=√x+√x
fonksiyonu için f (1) dege
Conheur
1
4√2
2√2
3
D) -¾/2
x²=₁²₁₁x
x ² + x 2
12/12/2.1 +
1+
1 X ²
2
7](https://media.kunduz.com/media/question/seo/raw/20230208163122311954-2452432.jpg?h=512)
n 16 E) 12 2. f(2x + 3) = x³ - 2x² + 1 olduğuna göre, f'(-1) kaçtır? A) 12 B) 11 C) 10 2 2. (3x² - 4x) 3+h D) 9 3 E) 8 20 IC 2. f(x)=√x+√x fonksiyonu için f (1) dege Conheur 1 4√2 2√2 3 D) -¾/2 x²=₁²₁₁x x ² + x 2 12/12/2.1 + 1+ 1 X ² 2 7